Metagenome-based insights into bacteriophage diversity of an urban river ecosystem - Abhiruchi Varshney; Indira P. Sarethy (Molecular Biology Reports, 2026)

Valorisation of acid casein whey via Chlorella sp. BB-32 cultivation: Growth optimisation and biochemical characterisation - C.R. Surana; P. Varshney; S.K. Saha; M. Callanan; O. McAuliffe (Bioresource Technology Reports, 2026)

Assessing the anaerobic biodegradability of PHB filament and its 3D printed sheets through biochemical methane potential (BMP) test - Anita Jena; Anjaly P. Thomas; Bijaya Bikram Samal; Brajesh Kumar Dubey; Cheruvu Siva Kumar; Shailendra Kumar Varshney (Science of The Total Environment, 2025)

Impact of heat stress on physiological characteristics and expression of heat shock proteins (HSPs) in groundnut (Arachis hypogaea L.) - B. Aravind; R. J. Shreeraksha; R. Poornima; Divyabharathi Ravichandran; P. U. Krishnaraj; V. P. Chimmad; Kiran K. Mirajkar; Basavaraj Bagewadi; Pasupuleti Janila; Manish K. Pandey; Rajeev K. Varshney; Spurthi N. Nayak (Physiology and Molecular Biology of Plants, 2024)

Transcriptome analysis of mantle and pearl sac of freshwater pearl mussel Lamellidens marginalis to identify biomineralisation-associated genes - Sonal Suman; A. Pavan-Kumar; Shailesh Saurabh; Vinaya Kumar Katneni; Sudheesh K. Prabhudas; Shubham Varshney; Sweta Pradhan; P. Gireesh-Babu; Rekha Das; Aparna Chaudhari (Molluscan Research, 2024)

Unraveling the diversity and functions of sugar transporters for sustainable management of wheat rust - Charu Lata; Anshul Sharma Manjul; Pramod Prasad; O. P. Gangwar; Sneha Adhikari; Sonu; Subodh Kumar; S. C. Bhardwaj; Gyanendra Singh; Mahesh Kumar Samota; Mukesh Choudhary; Abhishek Bohra; et al. (Functional & Integrative Genomics, 2023)

Influence of age, diurnal cycle, and plant and non-plant surfaces on oviposition by Spodoptera litura (Fabricius)(Lepidoptera: Noctuidae) - S. P. Yadav Deen; Anupam Varshney Sharma; Priya Singh; Satish Ganta; P. R. Ragesh; Smriti Sharma; Tarkeshwar; Kapinder; Jyotsna Singh; Mayanglambam Rojina Devi; Sanjiv Mullick (International Journal of Tropical Insect Science, 2023)

Genetic mapping of drought tolerance traits phenotyped under varying drought stress environments in peanut (Arachis hypogaea L.) - Subhasini Ghosh; Supriya S. Mahadevaiah; S. Anjan Gowda; Sunil S. Gangurde; Mangesh P. Jadhav; Anil A. Hake; P. Latha; T. Anitha; V. P. Chimmad; Kiran K. Mirajkar; Vinay Sharma; Manish K. Pandey; et al. (Euphytica, 2022)

Genetic mapping of tolerance to iron deficiency chlorosis in peanut (Arachis hypogaea L.) - Ankur D. Tayade; Babu N. Motagi; Mangesh P. Jadhav; Anjum S. Nadaf; Rajshekar V. Koti; Sunil S. Gangurde; Vinay Sharma; Rajeev K. Varshney; Manish K. Pandey; Ramesh S. Bhat (Euphytica, 2022)

Employing Drug Delivery Strategies to Overcome Challenges Using TLR7/8 Agonists for Cancer Immunotherapy - Dhruv Varshney; Sherry Yue Qiu; Tyler P. Graf; Kevin J. McHugh (The AAPS Journal, 2021)

Molecular mapping of dry root rot resistance genes in chickpea (Cicer arietinum L.) - Ashwini Karadi; Srinivasan Samineni; Sobhan Sajja; Mamta Sharma; Mahendar Thudi; Bingi P. Mallikarjuna; Kannalli P. Viswanatha; Rajeev K. Varshney; Pooran M. Gaur (Euphytica, 2021)

Genome-wide comparative transcriptome analysis of the A4-CMS line ICPA 2043 and its maintainer ICPB 2043 during the floral bud development of pigeonpea - Abhishek Bohra; Abhishek Rathore; Prasad Gandham; Rachit K. Saxena; S. J. Satheesh Naik; Dibendu Dutta; Indra P. Singh; Farindra Singh; Meenal Rathore; Rajeev K. Varshney; Narendra P. Singh (Functional & Integrative Genomics, 2021)

Identification of microRNAs and their gene targets in cytoplasmic male sterile and fertile maintainer lines of pigeonpea - Abhishek Bohra; Prasad Gandham; Abhishek Rathore; Vivek Thakur; Rachit K. Saxena; S. J. Satheesh Naik; Rajeev K. Varshney; Narendra P. Singh (Planta, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Development and characterisation of novel polymorphic microsatellite loci in the freshwater mussel Lamellidens marginalis (Lamarck, 1819) using next generation sequencing - Shubham Varshney; Madhavi Sagwekar; A. Pavan-Kumar; Rekha Das; P. Gireesh-Babu; Aparna Chaudhari; Gopal Krishna (Molluscan Research, 2020)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Integrating genomics for chickpea improvement: achievements and opportunities - Manish Roorkiwal; Chellapilla Bharadwaj; Rutwik Barmukh; Girish P. Dixit; Mahendar Thudi; Pooran M. Gaur; Sushil K. Chaturvedi; Asnake Fikre; Aladdin Hamwieh; Shiv Kumar; Supriya Sachdeva; Chris O. Ojiewo; et al. (Theoretical and Applied Genetics, 2020)
Key message Integration of genomic technologies with breeding efforts have been used in recent years for chickpea improvement. Modern breeding along with low cost genotyping platforms have potential to further accelerate chickpea improvement efforts. Abstract The implementation of novel breeding technologies is expected to contribute substantial improvements in crop productivity. While conventional breeding methods have led to development of more than 200 improved chickpea varieties in the past, still there is ample scope to increase productivity. It is predicted that integration of modern genomic resources with conventional breeding efforts will help in the delivery of climate-resilient chickpea varieties in comparatively less time. Recent advances in genomics tools and technologies have facilitated the generation of large-scale sequencing and genotyping data sets in chickpea. Combined analysis of high-resolution phenotypic and genetic data is paving the way for identifying genes and biological pathways associated with breeding-related traits. Genomics technologies have been used to develop diagnostic markers for use in marker-assisted backcrossing programmes, which have yielded several molecular breeding products in chickpea. We anticipate that a sequence-based holistic breeding approach, including the integration of functional omics, parental selection, forward breeding and genome-wide selection, will bring a paradigm shift in development of superior chickpea varieties. There is a need to integrate the knowledge generated by modern genomics technologies with molecular breeding efforts to bridge the genome-to-phenome gap. Here, we review recent advances that have led to new possibilities for developing and screening breeding populations, and provide strategies for enhancing the selection efficiency and accelerating the rate of genetic gain in chickpea.

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Identification of heterotic groups in South-Asian-bred hybrid parents of pearl millet - S. K. Gupta; K. Sudarshan Patil; Abhishek Rathore; Dev Vart Yadav; L. D. Sharma; K. D. Mungra; H. T. Patil; Suresh K. Gupta; Ramesh Kumar; Vaibhav Chaudhary; Roma R. Das; Anil Kumar; et al. (Theoretical and Applied Genetics, 2020)

Effect of elevated carbon dioxide and nitric oxide on the physiological responses of two green algae, Asterarcys quadricellulare and Chlorella sorokiniana - Prachi Varshney; John Beardall; Sankar Bhattacharya; Pramod P. Wangikar (Journal of Applied Phycology, 2020)

Drought and heat stress-related proteins: an update about their functional relevance in imparting stress tolerance in agricultural crops - Manu Priya; Om P. Dhanker; Kadambot H. M. Siddique; Bindumadhava HanumanthaRao; Ramakrishnan M. Nair; Sarita Pandey; Sadhana Singh; Rajeev K. Varshney; P. V. Vara Prasad; Harsh Nayyar (Theoretical and Applied Genetics, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

Identification of QTLs for resistance to Fusarium wilt and Ascochyta blight in a recombinant inbred population of chickpea (Cicer arietinum L.) - Tosh Garg; B. P. Mallikarjuna; Mahendar Thudi; Srinivasan Samineni; Sarvjeet Singh; J. S. Sandhu; Livinder Kaur; Inderjit Singh; Asmita Sirari; Ashwani K. Basandrai; Daisy Basandrai; Rajeev K. Varshney; et al. (Euphytica, 2018)

Marker-assisted introgression of resistance to fusarium wilt race 2 in Pusa 256, an elite cultivar of desi chickpea - Aditya Pratap; Sushil K. Chaturvedi; Rakhi Tomar; Neha Rajan; Nupur Malviya; Mahender Thudi; P. R. Saabale; Umashanker Prajapati; Rajeev K. Varshney; N. P. Singh (Molecular Genetics and Genomics, 2017)

Functionalized nanobiomaterials: high-performance sorbents for chromium remediation from water streams - P. Jain; S. Varshney; S. Srivastava (International Journal of Environmental Science and Technology, 2016)

Effect of high CO2 concentrations on the growth and macromolecular composition of a heat- and high-light-tolerant microalga - Prachi Varshney; Sujata Sohoni; Pramod P. Wangikar; John Beardall (Journal of Applied Phycology, 2016)

QTL mapping for late leaf spot and rust resistance using an improved genetic map and extensive phenotypic data on a recombinant inbred line population in peanut (Arachis hypogaea L.) - R. M. Kolekar; V. Sujay; Kenta Shirasawa; M. Sukruth; Y. P. Khedikar; M. V. C. Gowda; M. K. Pandey; R. K. Varshney; R. S. Bhat (Euphytica, 2016)

Detection of a new QTL/gene for growth habit in chickpea CaLG1 using wide and narrow crosses - L. Ali; S. Azam; J. Rubio; H. Kudapa; E. Madrid; R. K. Varshney; P. Castro; W. Chen; J. Gil; T. Millan (Euphytica, 2015)

MAGIC populations in crops: current status and future prospects - B. Emma Huang; Klara L. Verbyla; Arunas P. Verbyla; Chitra Raghavan; Vikas K. Singh; Pooran Gaur; Hei Leung; Rajeev K. Varshney; Colin R. Cavanagh (Theoretical and Applied Genetics, 2015)

Marker-trait association study for protein content in chickpea (Cicer arietinum L.) - A. A. JADHAV; S. J. RAYATE; L. B. MHASE; M. THUDI; A. CHITIKINENI; P. N. HARER; A. S. JADHAV; R. K. VARSHNEY; P. L. KULWAL (Journal of Genetics, 2015)

Genotyping-by-sequencing based intra-specific genetic map refines a ‘‘QTL-hotspot” region for drought tolerance in chickpea - Deepa Jaganathan; Mahendar Thudi; Sandip Kale; Sarwar Azam; Manish Roorkiwal; Pooran M. Gaur; P B Kavi Kishor; Henry Nguyen; Tim Sutton; Rajeev K. Varshney (Molecular Genetics and Genomics, 2015)

Genomics-assisted breeding in four major pulse crops of developing countries: present status and prospects - Abhishek Bohra; Manish K. Pandey; Uday C. Jha; Balwant Singh; Indra P. Singh; Dibendu Datta; Sushil K. Chaturvedi; N. Nadarajan; Rajeev K. Varshney (Theoretical and Applied Genetics, 2014)

Genetic dissection of drought tolerance in chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Mahendar Thudi; Spurthi N. Nayak; Pooran M. Gaur; Junichi Kashiwagi; Lakshmanan Krishnamurthy; Deepa Jaganathan; Jahnavi Koppolu; Abhishek Bohra; Shailesh Tripathi; Abhishek Rathore; Aravind K. Jukanti; et al. (Theoretical and Applied Genetics, 2014)

Captive Breeding and Embryonic Development of Butter Catfish (Ompok bimaculatus, Bloch 1794), a Threatened Fish of Indian Sub-continent in Northern India - Sudhir Raizada; K. K. Lal; U. K. Sarkar; P. K. Varshney; Vikash Sahu; Kailash C. Yadav; P. Agnihotri; A. Awasthi; J. K. Jena (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

An intra-specific consensus genetic map of pigeonpea [Cajanus cajan (L.) Millspaugh] derived from six mapping populations - Abhishek Bohra; Rachit K. Saxena; B. N. Gnanesh; Kulbhushan Saxena; M. Byregowda; Abhishek Rathore; P. B. KaviKishor; Douglas R. Cook; Rajeev K. Varshney (Theoretical and Applied Genetics, 2012)

Detection of Rotavirus from Hospitalized Diarrheic Children in Uttar Pradesh, India - S. K. Dash; Krishna Kumar; A. Tewari; P. Varshney; A. Goel; A. K. Bhatia (Indian Journal of Microbiology, 2012)

Identification and Characterization of Toxigenic Fusaria Associated with Sorghum Grain Mold Complex in India - Rajan Sharma; Ram P. Thakur; Senapathy Senthilvel; Spurthi Nayak; S. Veera Reddy; Veeranki Panduranga Rao; Rajeev K. Varshney (Mycopathologia, 2011)

Characterization of AhMITE1 transposition and its association with the mutational and evolutionary origin of botanical types in peanut (Arachis spp.) - M. V. C. Gowda; R. S. Bhat; V. Sujay; P. Kusuma; Varshakumari; S. Bhat; R. K. Varshney (Plant Systematics and Evolution, 2011)

A QTL study on late leaf spot and rust revealed one major QTL for molecular breeding for rust resistance in groundnut (Arachis hypogaea L.) - Y. P. Khedikar; M. V. C. Gowda; C. Sarvamangala; K. V. Patgar; H. D. Upadhyaya; R. K. Varshney (Theoretical and Applied Genetics, 2010)

Analysis of Genetic Diversity in Pongamia [Pongamia pinnata (L) Pierrre] using AFLP Markers - Mahendar Thudi; Revathi Manthena; Suhas P. Wani; Leela Tatikonda; David A. Hoisington; Rajeev K. Varshney (Journal of Plant Biochemistry and Biotechnology, 2010)

Integration of novel SSR and gene-based SNP marker loci in the chickpea genetic map and establishment of new anchor points with Medicago truncatula genome - Spurthi N. Nayak; Hongyan Zhu; Nicy Varghese; Subhojit Datta; Hong-Kyu Choi; Ralf Horres; Ruth Jüngling; Jagbir Singh; P. B. Kavi Kishor; S. Sivaramakrishnan; Dave A. Hoisington; Günter Kahl; et al. (Theoretical and Applied Genetics, 2010)

Diagnosis of gastrointestinal tuberculosis: Using cytomorphological, microbiological, immunological and molecular techniques — A study from Central India - Pradyumna Kumar Mishra; A. Bhargava; R. P. Punde; N. Pathak; P. Desikan; A. Jain; S. Varshney; K. K. Maudar (Indian Journal of Clinical Biochemistry, 2010)

Effect of vitamin E and selenium supplementation on oxidative stress indices and cortisol level in blood in water buffaloes during pregnancy and early postpartum period - Umesh Dimri; Rakesh Ranjan; Mahesh C. Sharma; V. P. Varshney (Tropical Animal Health and Production, 2010)

Genetics of ascochyta blight resistance in chickpea - R. Bhardwaj; J. S. Sandhu; Livinder Kaur; S. K. Gupta; P. M. Gaur; R. Varshney (Euphytica, 2010)

Effects of Nandrolone and TGF-β1 in growing rabbits with osteopenia induced by over-supplementation of calcium and vitamin D3 - H. P. Aithal; P. Kinjavdekar; Amarpal; A. M. Pawde; G. R. Singh; A. K. Pattanaik; V. P. Varshney; T. K. Goswami; H. C. Setia (Veterinary Research Communications, 2009)

Emission of isoprene from common Indian plant species and its implications for regional air quality - Rashmi Singh; Abhai Pratap Singh; M. P. Singh; Animesh Kumar; C. K. Varshney (Environmental Monitoring and Assessment, 2008)

Pharmacodynamic and pharmacokinetic characterisation of RBx 7796: a novel 5-lipoxygenase inhibitor - R. K. Shirumalla; P. Sharma; S. G. Dastidar; J. K. Paliwal; S. Kakar; B. Varshney; G. Singh Saini; V. Sattigeri; M. Salman; A. Ray (Inflammation Research, 2008)

ICA mixture model algorithm for unsupervised classification of remote sensing imagery - C. A. Shah; P. K. Varshney; M. K. Arora (International Journal of Remote Sensing, 2007)

A high density barley microsatellite consensus map with 775 SSR loci - R. K. Varshney; T. C. Marcel; L. Ramsay; J. Russell; M. S. Röder; N. Stein; R. Waugh; P. Langridge; R. E. Niks; A. Graner (Theoretical and Applied Genetics, 2007)

Endocrine Dysfunction in Chronic Severe Ehrlichiosis with or without Babesiosis in Dogs - A. Kumar; J. P. Varshney; V. P. Varshney (Veterinary Research Communications, 2006)

A Comparative Study on Oxidative Stress in Dogs Infected with Ehrlichia canis with or without Concurrent Infection with Babesia gibsoni - A. Kumar; J. P. Varshney; R. C. Patra (Veterinary Research Communications, 2006)

Genetic mapping and BAC assignment of EST-derived SSR markers shows non-uniform distribution of genes in the barley genome - R. K. Varshney; I. Grosse; U. Hähnel; R. Siefken; M. Prasad; N. Stein; P. Langridge; L. Altschmied; A. Graner (Theoretical and Applied Genetics, 2006)

Book review - P. K. Gupta; R. K. Varshney (Cereal Research Communications, 2004)

Development and validation of CAPS and AFLP markers for white rust resistance gene in Brassica juncea - A. Varshney; T. Mohapatra; R. P. Sharma (Theoretical and Applied Genetics, 2004)

Integrated physical maps of 2DL, 6BS and 7DL carrying loci for grain protein content and pre-harvest sprouting tolerance in bread wheat - R. K. Varshney; M. Prasad; J. K. Roy; M. S. Röder; H. S. Balyan; P. K. Gupta (Cereal Research Communications, 2001)

Establishment of genetic fidelity of In vitro-raised Lilium bulblets through rapd markers - Anushri Varshney; M. Lakshmikumaran; P. S. Srivastava; Vibha Dhawan (In Vitro Cellular & Developmental Biology - Plant, 2001)

A protocol for in vitro mass propagation of asiatic hybrids of lily through liquid stationary culture - Anushri Varshney; Vibha Dhawan; P. S. Srivastava (In Vitro Cellular & Developmental Biology - Plant, 2000)

Synergistic Effect of Polyamines on Bulblet Multiplication in Lillum sp (Asiatic Hybrids) - Anushri Varshney; Vibha Dhawan; P. S. Srivastava (Journal of Plant Biochemistry and Biotechnology, 2000)

The use of microsatellites for detecting DNA polymorphism, genotype identification and genetic diversity in wheat - M. Prasad; R. K. Varshney; J. K. Roy; H. S. Balyan; P. K. Gupta (Theoretical and Applied Genetics, 2000)

A microsatellite marker associated with a QTL for grain protein content on chromosome arm 2DL of bread wheat - M. Prasad; R. K. Varshney; A. Kumar; H. S. Balyan; P. C. Sharma; K. J. Edwards; H-Singh; H. S. Dhaliwal; J. K. Roy; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Identification of a microsatellite on chromosomes 6B and a STS on 7D of bread wheat showing an association with preharvest sprouting tolerance - J. K. Roy; M. Prasad; R. K. Varshney; H. S. Balyan; T. K. Blake; H. S. Dhaliwal; H-Singh; K. J. Edwards; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)